KAJIAN TARIF PEMADU MODA YOGYAKARTA INTERNASIONAL AIRPORT - Imam Basuki; Amos Setiadi; Benidiktus Susanto (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2019)
Abstract Yogyakarta International Airport in Temon, Kulon Progo, is projected as a replacement for Yogyakarta Adisu-tjipto International Airport. This new airport requires an intermodal passenger transport, which is a mode of transportation that needs to be prepared to connect the airport with the supporting cities served. In this study, a questionnaire survey involving 1,000 respondents was conducted. The survey was conducted at Adisutjipto Airport to find out the origin and destination of passengers in using the mode of transportation to and from Yogyakarta International Airport. Based on the origin and destination data, a map of the airport service area is made. The proportion of the choice of transportation mode was used as the basis of the potential passenger demand for a route. The route of intermodal transportation is found to be from and goes to 10 points, namely Borobudur, Kebumen, Magelang, Purwokerto, Purworejo, Temanggung, Wates/Sentolo, Wonosari, Wonosobo, and Yog-yakarta. The operational costs of intermodal passenger transport are Rp9,570.53 per kilometer. The average passenger fare per kilometer is Rp1,042.07. The tariff for various routes is more realistic in describing the distance, with an average deviation of Rp38.24 and a range of Rp141.55. Keywords: intermodal passenger transport, airport, tariffs, operational costs Abstrak Yogyakarta International Airport di Temon, Kulon Progo, diproyeksikan sebagai pengganti Bandar Udara Internasional Adisutjipto Yogyakarta. Bandar udara baru ini membutuhkan angkutan pemadu moda, yaitu suatu moda transportasi yang perlu dipersiapkan untuk menghubungkan bandar udara tersebut dengan kota-kota pendukung yang dilayani. Pada kajian ini dilakukan survei kuesioner yang melibatkan 1.000 responden. Survei dilakukan di Bandar Udara Adisutjipto untuk mengetahui asal tujuan dan keinginan penumpang dalam meng-gunakan moda transportasi untuk menuju dan dari Yogyakarta International Airport. Berdasarkan data asal dan tujuan dibuat peta daerah pelayanan bandar udara. Proporsi kemauan pemilihan moda transportasi menjadi dasar demand potensi penumpang untuk rute trayek. Rute trayek pemadu moda yang diperoleh berasal dan menuju ke-10 titik, yaitu Borobudur, Kebumen, Magelang, Purwokerto, Purworejo, Temanggung, Wates/Sentolo, Wono-sari, Wonosobo, dan Yogyakarta. Biaya Operasional Pemadu Moda adalah sebesar Rp9.570,53 per kilometer. Rata-rata tarif penumpang per kilometer adalah Rp1.042,07. Besaran tarif untuk berbagai rute trayek lebih realistis dalam menggambarkan jarak tempuhnya, dengan simpangan rata-rata Rp38,24 dan rentang sebesar Rp141,55. Kata-kata kunci: angkutan pemadu moda, bandar udara, tarif, biaya operasional